Effect of ion migration-induced electrode degradation on the operational stability of Perovskite solar cells - Rivkin, Boris; Sun, Qing; Taylor, Alexander D.; Vaynzof, Yana (ACS omega, 2018)
Perovskite-based solar cells are promising because of their rapidly improving efficiencies but suffer from instability issues. Recently, it has been claimed that one of the key contributors to the instability of perovskite solar cells is ion migration-induced electrode degradation, which can be avoided by incorporating inorganic hole-blocking layers (HBLs) in the device architecture. In this work, we investigate the operational environmental stability of methylammonium lead iodide perovskite solar cells that contain either an inorganic or organic HBL, with only the former effectively blocking ions from migrating to the metal electrode. This is confirmed by X-ray photoemission spectroscopy measured on the electrodes of degraded devices, where only electrodes of devices with an organic HBL show a significant iodine signal. Despite this, we show that when these devices are degraded under realistic operational conditions (i.e., constant illumination in a variety of atmospheric conditions), both types of devices exhibit nearly identical degradation behavior. These results demonstrate that contrary to prior suggestions, ion-induced electrode degradation is not the dominant factor in perovskite environmental instability under operational conditions.